Clinical and Serologic Characteristics of Systemic Lupus Erythematosus in the Arab World: A Pooled Analysis of 3,273 Patients - Marwan ADWAN, (Archives of Rheumatology, 2018)
Objectives: This study aims to describe the clinical and immunological characteristics of systemic lupus erythematosus in the Arab world. Materials and methods: We searched PubMed and Google Scholar for observational studies describing the clinical and serologic features of systemic lupus erythematosus in adult patients in the Arab world. We used the search terms “lupus in Arabs” and the names of individual Arab countries. Twenty-two articles from 11 countries including 3,273 patients (349 males, 2,924 females; mean age 28.9 years) met the inclusion criteria and were analyzed. Studies that reported on either clinical or serologic data in adult patients were included. Results: The mean age at disease onset was 28.9 years. The female to male ratio was 8.34:1. The most common clinical manifestations were arthralgia/arthritis (81.1%), anemia (55.6%), fatigue (53.4%), malar rash (53.1%) and renal manifestations (50.4%). Antinuclear antibodies were present in 97.2%, anti-double stranded deoxyribonucleic acid in 74.1%, anti-Ro/Sjögren syndrome A in 50.5%, anti-ribonucleoprotein in 43.5%, anti-Smith in 40.7% and anti-La/Sjögren syndrome B in 29.2%. The mortality rate was 7.6%. The frequency of various clinical and immunological manifestations varied between different regions. Conclusion: Systemic lupus erythematosus displays several different clinical and serologic characteristics, both among different Arab populations and in comparison to other ethnic groups.